ACCESS TO SEARCH AND DISSEMINATION OF INFORMATION ON GOVERNMENT ABOUT COMMUNICATION AND INFORMATICS BY SOCIETY IN SOUTH SULAWESI - Christiany Juditha (BPSDMP Kominfo Manado, 2017)
Current information abstraction into the general community needs. Information about good government, policy, program and the rules, especially the field of communication and information technology is important information to be known to the public. However, the problems facing Indonesia's vast territory requires the right strategy to disseminate information in order to come to the community. Besides, many people consider unimportant information on government. The purpose of the study is to get an overview of search access and dissemination of information on government field Kominfo by people in South Sulawesi (Makassar, Gowa, and North Toraja). The study used survei method with quantitative approach with 156 respondents. The study concluded that respondents were not too many take advantage of the government's official media Kominfo (central and local) to find information. Nevertheless some information topics of concern among respondents about the negative charge internet sites, public disclosure, the migration of analogue to digital TV, and UU ITE. Internet and social media are used by very few respondents in mengkases information while television and outdoor media (banner / billboard) became the most widely used. The majority of respondents also had forwarded the information obtained to family members and friends with a direct communication as well as via email, social media, and instant messanging. Keywords: information retrieval, dissemination of information, government information. Abstrak Saat ini informasi menjadi kebutuhan masyarakat umum. Informasi tentang pemerintah misalnya kebijakan, program maupun aturan khususnya bidang komunikasi dan informatika (kominfo) merupakan informasi penting diketahui masyarakat. Namun, masalah wilayah Indonesia yang luas membutuhkan strategi tepat untuk menyebarkan informasi agar sampai pada masyarakat. Disamping itu banyak masyarakat menganggap informasi tentang pemerintah tidak penting. Tujuan penelitian adalah untuk mendapatkan gambaran tentang akses pencarian dan penyebaran informasi tentang pemerintah bidang kominfo oleh masyarakat di Sulawesi Selatan (Makassar, Gowa, dan Toraja Utara). Penelitian menggunakan metode survei pendekatan kuantitatif dengan 156 responden. Hasil penelitian menyimpulkan bahwa responden tidak terlalu banyak memanfaatkan media resmi pemerintah bidang kominfo (pusat dan daerah) dalam mencari informasi. Meski demikian beberapa topik informasi yang menjadi perhatian responden diantaranya soal situs internet muatan negatif, keterbukaan informasi publik, migrasi TV analog ke digital, dan UU ITE. Internet dan media sosial sangat sedikit digunakan oleh responden dalam mengakses informasi sedangkan televisi dan media luar ruang (spanduk/baliho) menjadi media yang paling banyak digunakan. Mayoritas responden juga pernah meneruskan informasi yang diperoleh ke anggota keluarga dan teman dengan komunikasi langsung serta melalui email, media sosial, dan instant messanging. Kata Kunci: pencarian informasi, penyebaran informasi, informasi pemerintah